Modelling the interactions of zirconium hydrides. (August 2022) - Tondro, Alireza; Bidyk, Brooke; Ho, Ivan; Abdolvand, Hamidreza
Abstract: The zirconium alloys used in the core of nuclear reactors are susceptible to hydride formation and hydrogen embrittlement. Depending on the loading condition, zirconium hydrides usually form in different directions and with various configurations. This paper focuses on the development of the stress fields resulting from the interaction of hydrides, and the subsequent redistribution of hydrogen atoms. The effects of the separation distance between the hydrides formed in parallel and perpendicular configurations are investigated using a coupled diffusion-crystal plasticity finite element approach. The effects of hydride length and width on the stress-assisted diffusion of hydrogen atoms towards hydrides tips are also studied. It is shown that, due to the alignment of growth direction of hydrides, stress fields in the vicinity of two parallel hydrides interact more significantly compared to those of perpendicular hydrides. It is further shown that hydrides with a width of 1 µm propagate faster than those having lower or higher widths. Graphical Abstract: ga1